Factors related to Quality of Life in Patients with Obstructive Uropathy Receiving Percutaneous Nephrostomy - คล้ายชู, สุกัญญา; นาวีเจริญ, รุ้งระวี; จิตประไพ, ศิรส (Journal of The Royal Thai Army Nurses, 2019)
This research aimed to study the quality of life and to examine the relationships between symptom experiences, social support, severity of skin tissue damage and quality of life in patients with obstructive uropathy receiving percutaneous nephrostomy. Ninety-five participants using simple random sampling technique from those who had been diagnosed with obstructive uropathy due to pelvic malignancies receiving percutaneous nephrostomy more 3 months when who came to tertiary hospitals in Bangkok for their follow-up care and change percutaneous nephrostomy. Data were collected by using 5 parts of questionnaires: (1) Patient’s demographic data and treatment record forms, (2) The quality of life index, (3) The symptom experience assessment scale, (4) Social support questionnaire and (5) The skin assessment tool. Content validity was examined by five experts. Internal consistency reliability for the second, the third and the fourth parts of the questionnaires tested by Cronbach’s alpha coefficient were 91, .91 and .93, respectively. The skin assessment tool tested by inter-rater reliability was .90. Descriptive statistics, Pearson’s correlation and Spearman rank correlation coefficient were used in data analysis. The finding showed that the quality of life in the participants were at a moderate level (Mean = 66.34, SD = 14.55). Symptom experiences and severity of skin tissue damage were negatively related to the quality of life with statistical significance (r = -.54, r = -.35, respectively; p<.05). Social support was positively related to the quality of life with statistical significance (r = .27, p<.05).